Clinical Profile and Co-morbidities of Conduct Disorder and Oppositional Defiant Disorder in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Among juvenile behavior disorders, Conduct Disorder and Oppositional Defiant Disorder (ODD) are predominant ones and are of great concern because of their high degree of impairment.Materials & Methods: This descriptive cross-sectional study was conducted in the department of Psychiatry, Bangabandhu Sheikh Mujib Medical University and National Institute of Mental Health, Dhaka, during the period from August 2011 to November 2012 with sample size of 81. During data collection, semi-structured questionnaire designed by the researcher containing socio-demographic variables and Developments and Well–Being Assessment (DAWBA) – self, parent and teacher version were used.Results: Symptom profile showed that oppositional symptoms had no significant age or gender difference but aggressive symptoms, status offenses and property offenses were clearly more common among boys. Younger boys with Conduct disorder showed more aggressive symptoms, but status offense was more prevalent in older age group. Property offenses showed no age difference. Psychiatric co-morbidity was present in 48.1% respondents, among them; Attention- Deficit/Hyperactivity Disorder (ADHD) was highest (24.7%). ADHD was more prevalent in children with ODD and Major Depressive Disorder was more common in Conduct disorder. Total percentage of anxiety disorders was 14.8%.Conclusion: This was the first study in Bangladesh exploring the clinical profiles of Conduct disorder and Oppositional defiant disorder in hospital setting. Absence of control group and city based study places were the limitations of the research.J Bangladesh Coll Phys Surg 2020; 38(1): 29-34